Count everyone in: Operationalizing inclusion, diversity, equity, and accessibility in the work of an organizational Public Advisory Council - Ferreira-Legere, Laura; Yussuf-Homenauth, Sabella; Leong-Sit, Elise; Johnson, Simisola; Guttmann, Astrid; PAC, Past; Present Members ICES (International Journal of Population Data Science, 2026)
Objective Embedding public engagement within health data institutes, such as through public advisory councils (PACs), can strengthen the presence of public values and perspectives. Yet, common practices for operationalizing PACs often fail to include members from communities most impacted by health inequities. We addressed this gap by revising the operations of our PAC to strengthen inclusion, diversity, equity, and accessibility (IDEA) at ICES, a health data institute which holds administrative health data for the province of Ontario, Canada. Approach Our ICES PAC includes 15 members who advise on research and organization-level initiatives. During our fifth year of operation, we employed a mixed-methods strategy to incorporate feedback from members and evidence synthesis of IDEA best practices to embed IDEA into the PAC’s structure and function. Results We incorporated IDEA practices in three areas: recruitment, general operations, and member offboarding. The strategies were iterative and ongoing, with quantitative and qualitative evaluation embedded throughout. Incorporating IDEA practices in these areas broadened intersectional diversity in membership while also deepening our relationships with members, demonstrated by a 15% increase in members who felt heard and a 30% increase in members who felt the council reflected a range of diverse perspectives. Conclusion Our findings underscore that commitment to IDEA in PAC through equitable recruitment strategies, inclusive and accessible operations, and reflective member offboarding requires an iterative, ongoing process rather than a one-time objective. Implications: Health data institutes can strengthen the authenticity, effectiveness, and impact of their public advisory processes through commitment to IDEA principles and practices.